Wood anatomy of Forestiera (Oleaceae) species in Mexico - Ruiz-Valencia, Jesús Alejandro; Vázquez, Monserrat; Burgos-Hernández, Mireya; Gutiérrez, Jorge; Terrazas, Teresa (Instituto de Ecología, A.C., 2021)
Background and Aims: One of the most recent approaches to delimiting plant species is using anatomical wood characters in woody taxa, which has been little explored in Mexican representatives. The genera Forestiera is an example of this, since only the wood of two of the 12 species distributed in Mexico have been described. With the aim of contributing to the knowledge of the wood anatomy of the genera, as well as the search for anatomical characters that discriminate between their species, this study describes the wood anatomy of the wood of eight species of Forestiera distributed in Mexico, with a systematic approach. Methods: Wood from 42 wood samples from eight species were analyzed, with three individuals per species at 14 collection sites. The material was processed with conventional microtechniques to obtain qualitative and quantitative anatomical variables. Characters were evaluated with multivariate statistics to determine which ones are important to form groups of species in Forestiera. Key results: Some previously reported anatomical attributes agree with those observed in this paper. However, there are differences such as semi-ring porous wood and growth marks without marginal parenchyma. The analyses formed groups of species, based the diameter of early-wood vessels, length of vessel elements and fibers, diameter of the fibers, type of rays, abundance of the marginal parenchyma and the type of crystals in rays. Based on wood anatomy, a taxonomic key is proposed to identify the studied species. Conclusions: Through the used analyses, we contribute to the knowledge of Forestiera anatomy. Wood characters that allow to distinguish groups of species are recognized. Future studies will confirm their taxonomic value.